Epigenetics in osteoarthritis: Potential of HDAC inhibitors as therapeutics. (February 2018) - Khan, Nazir M.; Haqqi, Tariq M.
Graphical abstract: Abstract: Osteoarthritis (OA) is the most common joint disease and the leading cause of chronic disability in middle-aged and older populations worldwide. The development of disease modifying therapy for OA is in its infancy largely because the regulatory mechanisms for the molecular effectors of OA pathogenesis are poorly understood. Recent studies identified epigenetic events as a critical regulator of molecular players involved in the induction and development of OA. Epigenetic mechanisms include DNA methylation, non-coding RNA and histone modifications. The aim of this review is to briefly highlight the recent advances in the epigenetics of cartilage and potential of HDACs (Histone deacetylases) inhibitors in the therapeutic management of OA. We summarize the recent studies utilizing HDAC inhibitors as potential therapeutics for inhibiting disease progression and preventing the cartilage destruction in OA. HDACs control normal cartilage development and homeostasis and understanding the impact of HDACs inhibitors on the disease pathogenesis is of interest because of its importance in affecting overall cartilage health and homeostasis. These findings also shed new light on cartilage disease pathophysiology and provide substantial evidence that HDACs may be potential novel therapeutic targets in OA.